Experimental Studies on Some Clays Leading to Instability - Boubakeur Ykhlef; Abdelghani Belouar; Azdine Boulfoul (Civil Engineering Journal, 2023)
The landslide problem in the city of Constantine (Algeria) is mostly due to clayey soil, which is covering the whole area. Therefore, all the structures and foundations built over such soil are quite vulnerable. The sensitivity of this soil increases during the rainfall season, which might reach an extreme magnitude and cause damage to the structures. To understand some aspects of the failure of the mentioned soil and its mechanism, a large campaign of geotechnical characterization was undertaken using samples from the area. The specific gravity, Atterberg limits, and coefficient of lateral earth pressure at rest were determined. Samples were tested in triaxial stress path cells over a range of stresses, with the test being either stress- or strain-controlled, leading to sliding phenomena under different stress levels. The clays can be classified as over-consolidated soils. The test program and the characterization study indicated that Kois directly related to the stress history of the soil and also dependent upon the state of the sample before the test (i.e., undisturbed or disturbed). The clay minerals in the Mio-Pliocene landslide zones in Constantine are mostly montmorillonite and kaolinite, which have the lowest frictional resistance. As the montmorillonite content increases, the angle of internal friction decreases. The present study focuses on the critical state analysis since all the behavior problems of these tested samples show a peak shear strength, which is characteristic of over-consolidation materials that could lead to instability in this area. Doi: 10.28991/CEJ-2023-09-02-012 Full Text: PDF